The world of norm : may still be charged - Meres, Jonathan (London : Orchard Books, 2015)
Norm knew it was going to be one of those days when he was grounded before he'd even got up... But that's what happens when you run up a phone bill the size of a flipping bus. The trouble is Norm has no idea how it happened! All he knows is that he has to somehow pay it off if he's to go biking with Mikey. Even if that does mean going into business with the world's most annoying next door neighbor...
H
b
b
Keywords: Boys Fiction; Humorous Fiction; Discipline of Children